Clinical characteristics of 1,260 patients during an outbreak of carbapenem-resistant Acinetobacter spp in Porto Alegre, Brazil - Martins, Andreza Francisco (2014)
Introdution: Over the last decade, Acinetobacter baumannii has been an important cause of nosocomial infections worldwide. The objective of this study was to assess clinical and epidemiological characteristics of patients during a large citywide- documented outbreak of carbapenem-resistant A. baumannii (CRAb). Methods: Retrospective cross-sectional study that evaluated the information obtained from the official notification system data of CRAb from the Health Department, Porto Alegre, Brazil, in the period of July 1st, 2007 to December 31st, 2008. The association among variables was analyzed with SPSS 13.0. Results: A total of 1,260 CRAb from infection (608 [48.3%]) or colonization (652 [51.7%]) were reported in 18 hospitals. Most patients (53.5%) were hospitalized at intensive care units and have been exposed to invasive procedures, but 757 (60.7%) patients had no underlying comorbidity reported. A total of 1,143 (90.7%) patients received some antimicrobial 90 days before CRAb detection and 36.4% received a carbapenem. The outcome was available for 618 (49.0%) patients and 54.3% of them died. The prevalence ratio (PR) of infection was statistically significant for variables admission to public hospitals; trauma and use of antibiotic in previous 90 days.Conclusion: This study suggests that in the context of an outbreak, baseline comorbidities and previous carbapenem exposure may be less important risk factors for CRAb infection/colonization.